2012
DOI: 10.1021/ja308346b
|View full text |Cite
|
Sign up to set email alerts
|

Azurin as a Protein Scaffold for a Low-coordinate Nonheme Iron Site with a Small-molecule Binding Pocket

Abstract: The apo-protein of Pseudomonas aeruginosa azurin binds iron(II) to give a 1:1 complex, which has been characterized by electronic absorption, Mössbauer, and NMR spectroscopies, as well as X-ray crystallography and quantum-chemical computations. Despite potential competition by water and other coordinating residues, iron(II) binds tightly to the low-coordinate site. The iron(II) complex does not react with chemical redox agents to undergo oxidation or reduction. Spectroscopically-calibrated quantum-chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 123 publications
7
56
0
Order By: Relevance
“…8 These showed us that the existing correlations have few examples of multimetallic complexes, redox-active ligands, low-valent, and low-coordinate iron complexes. Additionally, the established correlations use continuum solvation models with the polarity of water 9b or methanol, 9d whereas the iron complexes of interest to our group are often studied experimentally in less polar solvents, such as toluene.…”
Section: Introductionmentioning
confidence: 99%
“…8 These showed us that the existing correlations have few examples of multimetallic complexes, redox-active ligands, low-valent, and low-coordinate iron complexes. Additionally, the established correlations use continuum solvation models with the polarity of water 9b or methanol, 9d whereas the iron complexes of interest to our group are often studied experimentally in less polar solvents, such as toluene.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports of iron substitution in azurin suggested that redox activity could only be achieved by altering the ligands in the binding site or using nuclear irradiation techniques such as cryoreduction. 27,60,61 Importantly, the Ni II/I couple remains physiologically accessible. Metalloenzymes containing low-valent nickel active sites have comparable reduction potentials, closely matched to the chemistry performed by those enzymes; the reduction potential of the proximal nickel center in ACS is observed at −540 mV.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Az has been used in many protein engineering studies and is robust towards mutation, serving as a tunable platform that imposes a well-defined secondary coordination sphere, which can modulate catalytic efficiency and selectivity. 20,21 …”
mentioning
confidence: 99%